2021
DOI: 10.3390/geriatrics6020041
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Poor Diet Quality, Physical Fatigability and Physical Function in the Oldest-Old from the Geisinger Rural Aging Study

Abstract: More perceived physical fatigability and poor diet quality are associated with impairments in physical function in older adults. However, the degree to which more perceived fatigability explains the association between poor diet quality and low physical function is unknown. We examined this relationship in 122 (66F, 56M) of the oldest-old participants from the Geisinger Rural Aging Study (GRAS). We used 24-h dietary recalls to assess the Healthy Eating Index (HEI), the Pittsburgh Fatigability Scale (PFS, 0–50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(73 reference statements)
0
5
0
Order By: Relevance
“… 78 In contrast, studies that assessed the associations of serum Zn with ADL 82 , 83 and instrumental activities of daily living did not report significant findings. 83 Davis et al 84 reported a low Zn intake in older adults with high perceived physical fatigability.…”
Section: Discussionmentioning
confidence: 99%
“… 78 In contrast, studies that assessed the associations of serum Zn with ADL 82 , 83 and instrumental activities of daily living did not report significant findings. 83 Davis et al 84 reported a low Zn intake in older adults with high perceived physical fatigability.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies found no association between diet quality and economic/physical function barriers to food access among older adults, 54,57 a few studies found an association between poor diet quality and economic and functional barriers to food access. 8,11,58,59 Inconsistencies in findings across studies may be attributed to several reasons. Studies use different methods in measuring diet quality, and some may be less sensitive in detecting such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Tsutsumimoto et al 24 reported that anorexia of aging was independently associated with exhaustion (OR = 1.39, 95% CI = 1.11–1.74, P = 0.004). Recently, Davis et al 25 explored how perceived fatigability explains the association between poor diet quality and low physical function. They found an inverse association between the Healthy Eating Index and the Pittsburgh Fatigability Scale Physical score.…”
Section: Discussionmentioning
confidence: 99%